2022
DOI: 10.3389/fonc.2022.953810
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic partial breast irradiation in primary breast cancer: A comprehensive review of the current status and future directions

Abstract: In selected low-risk breast cancer patients, accelerated partial breast irradiation (APBI) may represent an alternative option to the whole breast irradiation to reduce the volume of irradiated breast and total treatment duration. In the last few years, preliminary data from clinical trials showed that stereotactic partial breast radiotherapy may have the advantage to be less invasive compared to other APBI techniques, with preliminary good results in terms of local toxicity and cosmesis: the use of magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…TONIC trial demonstrated that SBRT (24Gy/3f) combined with nivolumab can increase the proportion of patients free of progression at 24 weeks than nivolumab alone (17% vs 8%) (Voorwerk et al, 2019). Another small sample research has indicated that preoperative with neoadjuvant chemotherapy may result in fair pCR rates of 36%, with the maximum response (pCR 67%) was obtained at a dose of 25.5Gy/3f (Bondiau et al, 2013), as well as no increase in the incidences of early or late-term adverse events (AEs) (Piras et al, 2023;Takanen et al, 2022). Together, these studies suggested SBRT may have strong immunomodulatory effects, rendering a synergistic antitumor effect with immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…TONIC trial demonstrated that SBRT (24Gy/3f) combined with nivolumab can increase the proportion of patients free of progression at 24 weeks than nivolumab alone (17% vs 8%) (Voorwerk et al, 2019). Another small sample research has indicated that preoperative with neoadjuvant chemotherapy may result in fair pCR rates of 36%, with the maximum response (pCR 67%) was obtained at a dose of 25.5Gy/3f (Bondiau et al, 2013), as well as no increase in the incidences of early or late-term adverse events (AEs) (Piras et al, 2023;Takanen et al, 2022). Together, these studies suggested SBRT may have strong immunomodulatory effects, rendering a synergistic antitumor effect with immunotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Partial breast irradiation after breast conserving surgery is an integral part of breast-conserving therapy for treatment of early-stage breast cancer (Njeh et al 2010). Several clinical trials have investigated the stereotactic partial breast irradiation (S-PBI) (Takanen et al 2022). In the S-PBI, accurate delineation of post-surgical clinical target volume (CTV) is a critical step for personalized and efficient treatment planning and delivery.…”
Section: Introductionmentioning
confidence: 99%